High prevalence of liver fibrosis among general population: a Romanian population-based study - Anca Trifan; Cristina-Maria Muzica; Robert Nastasa; Sebastian Zenovia; Ermina Stratina; Remus Stafie; Adrian Rotaru; Ana-Maria Singeap; Camelia Cojocariu; Catalin Sfarti; Irina Girleanu; Stefan Chiriac; et al. (Hepatology Communications, 2023)
Although high mortality is associated with liver cirrhosis, patients usually have a good quality of life in the compensated phase, and the disease may progress undiagnosed for many years. Vibration-controlled transient elastography with controlled attenuation parameter is a useful noninvasive tool used to estimate both the severity of fibrosis and steatosis. Hence, we aimed to establish the prevalence of significant liver fibrosis diagnosed by vibration-controlled transient elastography in an apparently healthy population. Between December 2021 and March 2022, we conducted a prospective screening of liver fibrosis in apparently healthy participants from different counties of Northeastern Romania. All subjects’ medical history was recorded through a comprehensive questionnaire and underwent a liver stiffness measurement. Participants with abnormal liver stiffness measurement values were further evaluated by laboratory tests to identify the etiology of chronic liver disease. A total of 127 apparently healthy subjects were enrolled, mainly females (59.8%), with a mean age of 56±11 years. Overall, 12.6% of participants were found to have significant to advanced fibrosis, and 5.4% had liver cirrhosis. Among 184 participants with clinically significant fibrosis (≥8.0 kPa), 26.1% had a history of heavy alcohol intake, 22.3% tested positive for hepatitis B and C infection, and 2.1% with other etiologies. The remaining 49.5% participants with clinically significant fibrosis were diagnosed with NAFLD, with a mean controlled attenuation parameter value of 282±34 dB/m. The high prevalence of significant liver fibrosis in the general population of Romania is alarming and should raise awareness among clinicians and public health systems. Vibration-controlled transient elastography has demonstrated its usefulness as a screening tool to identify advanced liver fibrosis in general population and should be used in liver disease prevention strategies.